Incidence, Outcomes, and Risk Factors for Isoniazid-Resistant Tuberculosis from 2012 to 2022 in Eastern China - Yan Shao; Wenlei Song; Honghuan Song; Guoli Li; Limei Zhu; Qiao Liu; Cheng Chen (MDPI AG, 2024)
Background: Isoniazid-resistant, rifampicin-susceptible tuberculosis (Hr-TB) is the most frequent drug-resistant tuberculosis (DR-TB) in the world, and unfavorable outcomes of Hr-TB are more common compared to drug-susceptible TB. Considering there is no optimal regimen accepted worldwide, we undertook a retrospective cohort study in eastern China to estimate incidence trends and risk factors associated with unfavorable outcomes of Hr-TB. Methods: Between January 2012 and December 2022, all Hr-TB patients' information was extracted from the Tuberculosis Information Management System (TIMS), which is a national electronic information platform, to record TB patients' clinical information in this study. The incidence of Hr-TB was determined by the mid-year population according to census data published by the government. We categorized treatment regimens depending on fluoroquinolone (FQ) use, and potential risk factors were analyzed using multivariable logistic regression. Results: A total of 3116 Hr-TB patients fulfilled the inclusion criteria and were enrolled in this study. The average annual rate of Hr-TB in the 11 years under investigation was 0.34 per 100,000 and increased to 0.53 per 100,000 until 2019. In total, six different treatment regimens were utilized in the study sites, and less than 1% of regimens adopted FQ. There was no difference in the unfavorable outcomes between the FQ-included and FQ-excluded groups (p = 0.22). The average treatment duration was 7.06 months, and the longest treatment was 26 months. Approximately 20% (637/3116) of Hr-TB patients had unfavorable outcomes, and 60.13% (383/637) of them proceeded to multidrug-resistant tuberculosis (MDR-TB). Treatment duration and a positive smear at the end of the 5th month were significantly associated with unfavorable outcomes (p < 0.001). Conclusion: The unfavorable treatment outcomes of Hr-TB are still high in eastern China, and the efficacy of FQ-containing regimens needs to be validated for Hr-TB treatment.